Technical Writing as Tralanguage in Favor of a Translation and Productemiccompetence of the Word - Djelloul, Said-Belarbi (Taikomoji kalbotyra, 2021)
In translation and traductology, specialists recognize the undeniable relationship between the act of transiting, technical writing and the meaning of the words. However, considerations regarding the problems presented by culture and realia (untranslatable terms) in particular are frequent. It is at the same time the raison d’etre of translation and the source of difficulties. In other words, building a sense of a word or even producing it in case of a failure in the target language is not easy, but is this exercise impossible? If not, what should be done to overcome these pitfalls and cultural difficulties for realia via a translation operation in general and a legal one in particular? Answers to these questions can be found in a proposal entailing a strategic approach, calling on four major factors that the “trauthor” should take into account for the production of the meaning of a word. Finally, a reflection on said factors is made to access the process of ways of teaching for the production of word meaning.
Keywords: technical writing; translation; traductology; legal word; meaning